2017
DOI: 10.3846/16484142.2017.1280851
|View full text |Cite
|
Sign up to set email alerts
|

Building on European Scientific Excellence to Develop an Educational Program on Intermodal Connections for Latvia and the Region

Abstract: Economic and social factors, including existing trends in urban population and employment growth combined with urbanization, have led to enhanced consumption and thus, increasing freight flows in the cities. Mitigation of transport impacts has led to plans towards a more sustainable urban environment. However, managerial and regulatory barriers restrict the incorporation of technological instruments and solutions to the sustainable dimension of decision-making and planning. This paper has sought to bridge this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…To achieve its goal, an on-line questionnaire survey was conducted by the Traffic, Transportation and Logistics Laboratory of University of Thessaly (Greece) and the Transport and Telecommunication Institute (Latvia), investigating the level of knowledge on transport interchanges and its importance. The survey was structured based on the 12 topics that resulted as educational requirements for sustainable transport interchanges, as they have been identified by Mitropoulos et al (2017a) and the 15 emerging trends identified by the collaboration of the EU and the US as regards the intermodal transportation (HORIZON 2020, Transportation Research Board, 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve its goal, an on-line questionnaire survey was conducted by the Traffic, Transportation and Logistics Laboratory of University of Thessaly (Greece) and the Transport and Telecommunication Institute (Latvia), investigating the level of knowledge on transport interchanges and its importance. The survey was structured based on the 12 topics that resulted as educational requirements for sustainable transport interchanges, as they have been identified by Mitropoulos et al (2017a) and the 15 emerging trends identified by the collaboration of the EU and the US as regards the intermodal transportation (HORIZON 2020, Transportation Research Board, 2016.…”
Section: Methodsmentioning
confidence: 99%
“…To address the specificities and complexity of the domain of transport interchanges, Mitropoulos et al (2017a) implemented gap analysis and studied the trends in transport interchanges and the available European educational programs. They identified the knowledge requirements for Latvia and the Baltic Region, as modest innovation performance states (European Commission, 2014a), with low expenditure in high education and business enterprise (European Commission, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the results of ALLIANCE project analysis existing research, educational and training programs in transport in Latvia and the Baltic Sea region present an adequate coverage of traditional transport principles and the generic methods that are used in transport for planning and design. However, the first result of deep analysis showed that these courses are not specialized on intermodality (Mitropoulos et al 2017). It is possible to claim, that the transport education in Baltic countries is national oriented from the point of view of content, language and training material, and therefore integration of the Baltic transport networks with the European transport network should be especially included in transport programmes.…”
Section: State Of the Artmentioning
confidence: 99%
“…STIP was developed within the frame of the ALLIANCE project (Nathanail et al 2016b) and has been implemented and approbated during the 1st ALLIANCE Summer School in Riga (Latvia) in July 2017. The program's development followed a thorough analysis of the needs analysis, which revealed the required skills and knowledge for professionals in the domain of transport interchanges by Mitropoulos et al (2017). The analysis included identification of the requirements for sustainable passenger and freight interchanges, assessment of relevant educational programs and specific topics covered in European Universities, categorization of them into educational areas, and finally composition of twelve course modules comprising the core curriculum of STIP.…”
Section: Formulation Of the Educational And Training Topicsmentioning
confidence: 99%
See 1 more Smart Citation